2015
DOI: 10.1186/s12864-015-1833-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and gene expression dynamics during spermatogonial stem cell differentiation in the early postnatal mouse testis

Abstract: BackgroundIn the male germline, neonatal prospermatogonia give rise to spermatogonia, which include stem cell population (undifferentiated spermatogonia) that supports continuous spermatogenesis in adults. Although the levels of DNA methyltransferases change dynamically in the neonatal and early postnatal male germ cells, detailed genome-wide DNA methylation profiles of these cells during the stem cell formation and differentiation have not been reported.ResultsTo understand the regulation of spermatogonial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 79 publications
(132 reference statements)
10
135
0
Order By: Relevance
“…However, these genes/loci attain their full/expected imprinting prior to puberty. In contrast, the high-OCT4/ ID4 subtypes displayed expected paternal imprints throughout postnatal development, supporting recent work in high-OCT4 neonatal SSCs (Kubo et al 2015). Here we note that the subset of THY1 + and KIT + spermatogonia that shows both imprinting defects and mesenchymal-like features may contribute to the pool of spermatogonia that participates in the first wave of gametogenesis (Yoshida et al 2006).…”
Section: Dynamics Of Imprinting In Developing Germline Stem Cellsmentioning
confidence: 48%
“…However, these genes/loci attain their full/expected imprinting prior to puberty. In contrast, the high-OCT4/ ID4 subtypes displayed expected paternal imprints throughout postnatal development, supporting recent work in high-OCT4 neonatal SSCs (Kubo et al 2015). Here we note that the subset of THY1 + and KIT + spermatogonia that shows both imprinting defects and mesenchymal-like features may contribute to the pool of spermatogonia that participates in the first wave of gametogenesis (Yoshida et al 2006).…”
Section: Dynamics Of Imprinting In Developing Germline Stem Cellsmentioning
confidence: 48%
“…DNA cytosine modification is a dynamic process catalyzed by specific DNA methyltransferases (DNMTs) that convert cytosine (C) to 5-methylcytosine (abbreviated 5mC or M; Bestor, Laudano, Mattaliano, & Ingram, 1988; Okano, Xie, & Li, 1998), usually within the sequence context of CpG (Bestor et al, 1988; Okano, Bell, Haber, & Li, 1999; Okano et al, 1998) or CpA (Gowher & Jeltsch, 2001; Kubo et al, 2015; Lister et al, 2013, 2009; Ramsahoye et al, 2000; Vlachogiannis et al, 2015). A subset of 5mC may then be oxidized to 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC) by the ten-eleven translocation (Tet) dioxygenases in three consecutive Fe(II) and α-ketoglutarate-dependent oxidation reactions (He et al, 2011; Ito et al, 2010, 2011; Tahiliani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that DNA methylation occurs not only at promoter regions but also at other regulatory regions (Khalid et al, 2014; Kubo et al, 2015; Rea et al, 2017). We therefore asked if these changes in 5hmC occur at other functional genomic regions as well.…”
Section: Resultsmentioning
confidence: 90%